Adjusting the Course Structure for Facilitating the MBKM Program - Victa Sari Dwi; Adhi Kusuma; Sri Lestari Yuli Prastyatini; Indra Kurniawan; Kewwalee Kumyai (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2022)
The current case study was to analyze the course credit conversion of MBKM experienced by 40 university students who join the student exchange and pre-teacher service. Through the individual interviews among the participants, the study found that there were several reasons why they join the MBKM programs. However, started from the piloting program of both MBKM, the credit conversion has still become the main problem not only among students, but also the university. The discussion was brought under the scope of the structure of the spreading of course unit throughout the semesters. The study suggests that the courses should be redesigned by placing the main course at the beginning of the course: semester one to three, and the last semester. Whereas, the semesters depicted to MBKM were on semester five to seven. It means that the converted course units were on semester five to seven as well.